Impacts of Salinity and Temperature on the Thyroidogenic Effects of the Biocide Diuron in Menidia beryllina - Moreira, Lucas Buruaem [UNESP]; Diamante, Graciel; Giroux, Marissa; Coffin, Scott; Xu, Elvis Genbo; Abessa, Denis Moledo de Souza [UNESP]; Schlenk, Daniel (Amer Chemical Soc, 2018)
Diuron is a herbicide used in agricultural and urban settings and also as an antifouling agent. Recent studies have indicated sublethal responses of diuron in the endocrine system of fish and amphibians. Given the potential of climate change to also alter fish endocrinology, the combination of environmental stressors with diuron may contribute to its sublethal toxicity. In this study, the effects of temperature and salinity on thyroid targets of diuron were assessed in juveniles of the estuarine fish Menidia beryllina under different conditions of salinity (10 and 20 parts per thousand) and temperature (10 and 20 degrees C). Environmentally relevant concentrations of diuron affected the growth, and the higher temperature reduced the condition factor of animals. Increased levels of T3 were observed in fish from all treatments, and at 10 degrees C, T4 levels were augmented at 10 parts per thousand but reduced at 20 parts per thousand. Increased gene expression of deiodinases at 20 parts per thousand in both temperatures suggests the influence of salinity on the regulation of hormone imbalance via deiodination pathway activation. Decreased transcripts of thyroid and growth hormone receptors were also observed following diuron treatment. These results indicate that changes in environmental stressors may have significant impacts on the ecological risk of diuron in estuarine fish.